Optimization of quaternion based on hybrid PID and Pw control - Balya, Darohini; M. F., Abas; Pebrianti, Dwi; Hamzah, Ahmad; M. H., Ariff; M. R., Arshad (2019)
The aim of this article is to present an optimization of full non-linear quaternion based on hybrid control scheme using Genetic Algorithm (GA). A wider objective is used to find novel solutions to design hybrid controller based on PID and Pω control so that system functionality and performance may be compromised. In the presented approach both the quadrotor’s attitude model and the proposed hybrid control algorithm have been implemented in the fully quaternion space without any transformations or conversion and calculations in the Euler’s angles. In this paper, the optimized quaternion with fitness function composed of